Assessment of graphene oxide ecotoxicity at several trophic levels using aquatic microcosms. (January 2020) - Evariste, Lauris; Mottier, Antoine; Lagier, Laura; Cadarsi, Stéphanie; Barret, Maialen; Sarrieu, Cyril; Soula, Brigitte; Mouchet, Florence; Flahaut, Emmanuel; Pinelli, Eric; Gauthier, Laury
Abstract: Extensive development of new applications using graphene based materials such as graphene oxide (GO) increases its potential release and occurrence into aquatic environments, raising the question of its biological and ecological risks. As standardized single-species-based assays fail to highlight toxicological pathways implying interactions between organisms, the use of micro/mesocosms appears as a good solution to fill the lack of environmental realism inherent to these tests. In this work, experiments were achieved using microcosm systems to expose a reconstituted food chain to GO at environmentally-relevant concentrations (0.05 and 0.1 mg L −1 ). The trophic chain was composed of a consortium of algae and bacteria as primary producers, chironomid larvae as primary consumers and decomposers while larvae of the amphibian Pleurodeles waltii constituted the secondary consumers. Monitoring of multiple ecotoxicological and ecological endpoints allowed to observe changes in bacterial communities while no toxic effects were noticed in chironomids. However, chironomids feeding behaviour changed as a consequence of GO contamination, leading to an increase in leaf litter consumption. Genotoxic effects were noticed in Pleurodeles larvae. This study highlights the importance of using such experimental systems to better encompass the ecotoxic potential of GO through the determination of toxicological routes and consequences on ecosystem's functioning. Graphical abstract: Image 1